Analysis of Science Literacy and Adversity Quotient on the Implementation of Problem Based Learning Model Assisted by Performance Assessment - Aliyana, Aliyana; Saptono, Sigit; Budiyono, Budiyono (Universitas Negeri Semarang, 2019)
Science literacy is one of the problems of education in Indonesia that needs attention to be resolved immediately. The ability of science literacy in Indonesia is still low, which is evidenced by the International agency Organization for Economic Cooperation and Development (OECD) through the Programme for International Student Assessment (PISA) to Children aged 15 years. This study aimed to (1) determine the effectiveness of Problem Based Learning (PBL) aided by Performance Assessment of students 'scientific literacy abilities and , (2) to describe the students' scientific literacy abilities reviewed by Adversity Quotient (AQ). This research used a quasi-experiment with a pretest-posttest control group design. The sample of this study ware students IV A (experimental group) and class IV B (control group) in SDN 1 Purwawinangun Cirebon. In this study data were taken using test instruments and questionners. Data analysis used were the normality test, the homogeneity test, and the average similarity test. Obtained data indicate that the class taken as samples in this study were normally distributed and have homogeneous variances. It means that the sample comes from the same condition that was having the same knowledge. N-gain test showed that the experimental group was 0.31 score as the medium category and the control group was 0.29 score as the low category. The finding showed that PBL model aided by performance assessment was effective for increasing students' scientific literacy ability were which indicated by student’s with PBL learning aided by performance assessment was by achieving complete scientific literacy on PBL aided by performance assessment better than students on PBL. The pattern of science literacy ability reviewed by AQ; a) climber students type were able to master both of the aspects applying and designing problem strategies. b) camper type students were mastered both of the aspect reasoning and able analyzed that given problems. c) quitter type students have ably mastered only the knowing aspect.